2021
DOI: 10.3390/uro1010002
|View full text |Cite
|
Sign up to set email alerts
|

Comparing World Health Organization/International Society of Urological Pathology Grading and Fuhrman Grading with the Prognostic Value of Nuclear Area in Patients with Renal Cell Carcinoma

Abstract: This study was undertaken to compare Fuhrman grading with World Health Organization/International Society of Urological Pathology (WHO/ISUP) grading and stereologically measured nuclear area in patients with Clear Cell Renal Cell Carcinoma (ccRCC) or Papillary Renal Cell Carcinoma (PRCC) and to evaluate the independent predictive value of Fuhrman, WHO/ISUP and stereologically measured nuclear area combined with necrosis in a series of patients with ccRCC in relation to cancer-specific survival. In all, 124 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The nuclear grades I to III are relatively interchangeable between these two systems. 27 The grade IV in the Fuhrman system, whereas the ISUP-WHO grading system includes rhabdoid and sarcomatous tumor cells in the grade IV category. 27 These types of tumor cells were analyzed separately from nuclear grading, and the presence of sarcomatoid tumor cells was found to independently correlate with a diagnosis of atypia or above.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear grades I to III are relatively interchangeable between these two systems. 27 The grade IV in the Fuhrman system, whereas the ISUP-WHO grading system includes rhabdoid and sarcomatous tumor cells in the grade IV category. 27 These types of tumor cells were analyzed separately from nuclear grading, and the presence of sarcomatoid tumor cells was found to independently correlate with a diagnosis of atypia or above.…”
Section: Discussionmentioning
confidence: 99%
“…The original Fuhrman and WHO/ISUP grading systems represent methods that assess the nuclear morphology in renal cell carcinoma to predict prognosis. 4 , 17 , 18 The present study used the modified versions as shown in Table 1 . The highest grade in the specimen was adopted in either grading system, as in the original ones.…”
Section: Methodsmentioning
confidence: 99%
“…These characteristics are often used to distinguish between benign and malignant tumors and to predict prognosis in many malignancies. 1 , 2 , 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the ISUP grading system relies only on the size of the nucleolus for grading tumors 1-3 and on the presence of giant cells or, the presence of sarcomatoid differentiation or RD features for assigning grade 4 (18,29). Previously, several studies compared Furman grading with WHO/ISUP grading (55,56). In these studies, the WHO/ISUP grading was shown to provide superior prognostic information compared to Fuhrman grading (55,56).…”
Section: Isup N Grading System --------------------------------------...mentioning
confidence: 99%
“…Previously, several studies compared Furman grading with WHO/ISUP grading (55,56). In these studies, the WHO/ISUP grading was shown to provide superior prognostic information compared to Fuhrman grading (55,56). Therefore, the regrading of the kidney tumors in the research databases could be a reasonable procedure.…”
Section: Isup N Grading System --------------------------------------...mentioning
confidence: 99%